Dziekani Wydziału Prawa Uniwersytetu we Wrocławiu w latach 1811-1911 - Dolata, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The aim of the article is to shed some light on the figures of professors serving as deans in the first one hundred years of the Faculty of Law at the German University of Wrocław. However, the author’s intention is to analyse not their scholarly achievements, but, rather, the individual career paths in the organisational sphere of the leading figures of German jurisprudence. The author points to the term limit applying to the office of dean and the age structure of the German professors appointed deans of the Faculty of Law. In addition, he presents the academic careers of all 34 deans and points to some patterns in appointments to the office
Keywords: University of Wrocław; Faculty of Law of the University of Wrocław in 1811– 1911; deans of the Faculty of Law in 1811–1911; teaching of law at the Faculty of Law of the University of Wrocław in 1811–1911